EXPERIMENTAL DETERMINATION OF ANORTHITE SOLUBILITY AND CALCIUM SPECIATION IN SUPERCRITICAL CHLORIDE SOLUTIONS AT 2 KB FROM 400 TO 600°C - Roselle G.T.; Baumgartner L.P. (My University, 1995)
The solubility of the assemblage anorthite + andalusite + quartz and Ca speciation were investigated in supercritical chloride solutions between 400 and 600°C at 2 kb over a total chloride range of 0.005-5.6 m. Species interpretation is based on systematic regression of multiple speciation schemes by a nonlinear, weighted least squares procedure. Best fits to the data were obtained by including the Ca species CaCl-3 and Ca(OH)+, in addition to the species Ca2+, CaCl+, CaCl02, H+, OH-, Cl-, H2O, Al(OH)03, H4SiO04, and HCl0. The logarithm of the equilibrium constant for the reaction CaAl2Si2O8 + 2HCl = CaCl02 + Al2SiO5 + SiO2 + H2O is given by: log K3 = -17.13 (+/-0.41) + 16483 (+/-301)T (K).For the reaction, Ca(OH)+ = Ca2+ + OH-: log K18 = -35.39 (+/-0.41) + 22558 (+/-283)T (K) was obtained. The logarithm of the dissociation constant for the reaction CaCl-3 = CaCl2 + Cl- was determined at 600°C to be -1.317 (+/-0.15).The formation constants for Ca-chloride species determined in the present study are in close agreement with those retrieved by Baumgartner (1991) from the wollastonite + quartz solubility data of Popp and Frantz (1979), which were obtained over a smaller range of total chloride concentration. Prediction of the dissociation constant for the portlandite hydrolysis reaction was made based on the present anorthite solubility data and is in excellent agreement with the portlandite solubility data of Walther (1986). Results of calculations on the solubility of the assemblage plagioclase + muscovite + andalusite + quartz indicate that the dominant Ca species are either Ca(OH)+ or CaCl-3 depending on total chloride concentration. With the formation of CaCl-3, increased solubility of calcium in saline fluids is predicted, relative to Na and K.